Overexpression of MdNRT2.4 Improved Low-Nitrogen Tolerance in Transgenic Tobacco Lines - Junrong Li; Ke Liu; Chunqiong Shang; Qiandong Hou; Xiangmei Nie; Qinglong Dong; Dong Huang; Qian Wang (Horticulturae, 2025)
Apple (Malus domestica Borkh.) is an economically important fruit. The use of nitrate by plants plays a crucial role in their growth and development, and its absorption and dispersal are controlled by nitrate transport proteins (NRTs). In this study, we investigated the potential function of MdNRT2.4 under low-nitrogen (N) stress by overexpressing it in tobacco. Compared with plants treated with a normal nitrogen level (5 mM), the MdNRT2.4 overexpression lines under low-N stress (0.25 mM) exhibited significantly greater plant height and width, as well as larger leaves and a higher leaf density, than wild-type plants, suggesting that the overexpression of MdNRT2.4 enhances the low-N tolerance of tobacco. Enhanced antioxidant enzyme activities in the MdNRT2.4 overexpression plant lines promoted the scavenging of reactive oxygen species, which reduced damage to their cell membranes. GUS staining of pMdNRT2.4::GUS-transformed Arabidopsis thaliana lines showed that MdNRT2.4 was expressed in the roots, vascular bundles, seeds in fruit pods, and young anther sites, suggesting that MdNRT2.4 mediates the transport of nitrate to these tissues, indicating that MdNRT2.4 might promote nitrate utilization in apple and improve its tolerance to low-N stress. Experiments using yeast one-hybrid and dual-luciferase assays revealed that MdbHLH3 binds to the MdNRT2.4 promoter and activates its expression. MdbHLH3 belongs to the basic helix–loop–helix (bHLH) transcription factor (TF). It is speculated that MdbHLH3 may interact with the promoter of MdNRT2.4 to regulate N metabolism in plants and enhance their low-N tolerance. This study establishes a theoretical framework for investigating the regulatory mechanisms of low-N responsive molecules in apple, while simultaneously providing valuable genetic resources for molecular breeding programs targeting low-N tolerance.